2021
DOI: 10.1186/s13020-021-00536-w
|View full text |Cite
|
Sign up to set email alerts
|

Acupressure in patients with seasonal allergic rhinitis: a randomized controlled exploratory trial

Abstract: Background Acupuncture has shown beneficial effects for seasonal allergic rhinitis (SAR); however, it is time and cost intensive. We investigated feasibility and effects of self-administered body acupressure as a self-care technique that stimulates acupuncture points with manual pressure in SAR patients. Methods We conducted a two-armed randomized controlled exploratory trial to compare effects of self-administered acupressure over 4 weeks at five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
4
0
1
Order By: Relevance
“…Akupunkturpunkte können jedoch nicht nur genadelt werden. Der Einsatz von Akupressur zeigte in einer Pilotstudie gegenüber der Warteliste erstaunlich gute Effekte, wenn eine Kombination aus Di 4, 11, 20, Gb 20 und Ex 1 über 4 Wochen täglich insgesamt 15 Minuten durch Patient*innen selbst akupressiert wurden 18 .…”
Section: Akupunkturpraxisunclassified
“…Akupunkturpunkte können jedoch nicht nur genadelt werden. Der Einsatz von Akupressur zeigte in einer Pilotstudie gegenüber der Warteliste erstaunlich gute Effekte, wenn eine Kombination aus Di 4, 11, 20, Gb 20 und Ex 1 über 4 Wochen täglich insgesamt 15 Minuten durch Patient*innen selbst akupressiert wurden 18 .…”
Section: Akupunkturpraxisunclassified
“…Self-administered acupressure and hydrotherapy, according to the German non-medical naturopath and priest Sebastian Kneipp, showed little to no side effects. [35,36,[43][44][45] As there is good evidence for the effectiveness of acupuncture in patients with RLS, and some pilot studies have shown that acupressure and cold applications can reduce RLS-and sleep-related symptoms, we hypothesized that self-administered acupressure and Kneipp hydrotherapy with cold affusions could be a potential therapeutic option for patients with RLS.…”
Section: Background and Rationalementioning
confidence: 99%
“…Self-administered acupressure and hydrotherapy, according to the German non-medical naturopath and priest Sebastian Kneipp, showed little to no side effects. [35,36,43–45]…”
Section: Introductionmentioning
confidence: 99%
“…From the beginning, a combination of research, clinical practice, and teaching was endorsed. Therefore, many high-quality randomized controlled trials, such as on acupuncture [11, 12], acupressure [13], and osteopathic medicine [12, 14], were conducted in the OPD. The designated studies investigated treatment options for chronic conditions including chronic musculoskeletal pain and atopic conditions.…”
Section: Introductionmentioning
confidence: 99%